Kinerja Efisiensi Biaya Dengan Metode Data Envelopment Analysis (DEA) - Nazmil Umri; Rachmad Hidayat; Issa Dyah Utami (JURNAL TEKNIK INDUSTRI, 2011)
Target of research with Data method of Envelopment Analysis ( DEA) is to determine efficiency storey; level of expense of and factor - factor having an effect on to efficiency of expense of in office of branch of Perum Pawnship office of region of Bangkalan. Result of this research is got by branch of Perum inefficient Pawnship office is Perum Pawnship office of Bangkalan with efficiency storey; level equal to 0,144236, Perum pawnship office of Kamal in januari 2009 with Storey; Level Efficiency equal to 0,3650507,pada months of Februari 2009 equal to 0,4614362 and in March 2009 equal to 0,2610103 until March 2009 and Perum pawnship office of Foreland Earth with its Efficiency storey; level is equal to 0,1390164 pada March months 2009.